Development of Sales Modules for Agricultural E-Commerce Using Dynamic System Development Method - Rosa Delima; Halim Budi Santoso; Gerry Herbiyan Aditya; Joko Purwadi; Argo Wibowo (IJNMT (International Journal of New Media Technology), 2018)
E-Commerce is a process model of selling and buying goods using information and communication technology. This business model offers a broad market for products owned by the seller. However this sales model is not yet common for agricultural products. Most of the process of buying and selling agricultural products is still done conventionally. The lack of agricultural e-commerce sites is the main reason for the research conducted. This research will develop an agricultural e-commerce system. This system has two main modules that are sales module and purchasing module. This article specifically develops sales modules for agricultural e-commerce. In the development of modules applied Dynamic System Development Method. The used of this model is based on characteristic of the project which have limited number of development team and short development time. The development stages consist of pre-project, feasibility study, business study, functional model iteration, and design and build iteration. In this study a prototype has been produced for the sales module on agricultural e-commerce that is being developed